Hermenêutica e teoria da ação em o si-mesmo como um outro de Paul Ricoeur - Corá, Élsio José (2004)
This dissertation talks about the concepts of hermeneutic and theory of action in Paul Ricoeur (1913) The emphasis of the analysis focus between teleology and deontology, show the attempt of anchoring the hermeneutic in the phenomenological method. It s shown that the consciousness becomes task, while being comprehension of signs and symbols and texts. The hermeneutic concept of oneself is understood through its two poles: sameness-identity and self-hood-identity. Its implications regard to the action theory allow to bring about that the ethic perspective of aiming a good life with and to others in fair institutions , which guides the capable man picture it is the articulator line of the relation between moral and ethic. It s also shown that the relation between teleology an deontology is done inside a dialectic process which enables the primacy of the ethic over the moral.